2004
DOI: 10.1021/jf0496853
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Harvest Year Effects on Near-Infrared Reflectance Spectroscopic Analysis of Olive (Olea europaea L.) Fruit Traits

Abstract: The influence of parent and harvest year on the determination of oil, moisture, oleic acid, and linoleic acid contents in intact olive fruit was studied by near-infrared spectroscopy (NIRS). Spectral data from 400 to 1700 nm were recorded on 437 fruit samples collected in 1996 and 1997 from seedling plants derived from three different female parents. Partial least squares models were developed using samples for each year and for each female parent separately and were validated against the other groups. Calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 21 publications
(24 reference statements)
7
33
0
Order By: Relevance
“…Leon et al (2003) obtained regression models by partial least squares (PLS) and NIRS, with predictive errors sufficiently small, for the analysis of oil content (R 2 ϭ 0.83), moisture (R 2 ϭ 0.88) and fatty acid composition (R 2 from 0.77 to 0.81 for oleic and linoleic) in intact olives, as a useful tool in olive breeding programmes. Finally, as part of an olive tree breeding program, the same authors (Leon et al, 2004) reported the influence of the parents and the harvest year, on oil content , moisture and fatty acids determined by NIRS analysis of intact olives, with the same calibration results as previously mentioned.…”
Section: Introductionmentioning
confidence: 82%
“…Leon et al (2003) obtained regression models by partial least squares (PLS) and NIRS, with predictive errors sufficiently small, for the analysis of oil content (R 2 ϭ 0.83), moisture (R 2 ϭ 0.88) and fatty acid composition (R 2 from 0.77 to 0.81 for oleic and linoleic) in intact olives, as a useful tool in olive breeding programmes. Finally, as part of an olive tree breeding program, the same authors (Leon et al, 2004) reported the influence of the parents and the harvest year, on oil content , moisture and fatty acids determined by NIRS analysis of intact olives, with the same calibration results as previously mentioned.…”
Section: Introductionmentioning
confidence: 82%
“…The NIR prediction of fruit moisture and oil content in intact olives has been previously reported. León et al (2003León et al ( , 2004 The different cultivars evaluated in this work showed differences in lipid synthesis both in total amount of oil formed and the period of time, as well as the evolution of fruit moisture during ripening (Figures 3 and 4). The prediction values for oil content and moisture by cultivar and sampling date were closely correlated with reference A. GRACIA AND L. LEÓN values both for trial 1 (on-tree prediction) and 2 (laboratory prediction).…”
Section: Calibration Development For Each Trial Setmentioning
confidence: 60%
“…In olives, previous works have demonstrated the enormous possibilities offered by NIR spectroscopy for the on site quality control process of olive fruits, pastes, and oils for both a quantitative analysis of the main components or the discrimination of samples according to cultivar, origin, common olive alterations, classification, authentication and detection of olive oils (reviewed by Armenta et al 2010). However, direct analysis of intact fruit has been scarcely reported (León et al, 2003(León et al, , 2004Cayuela et al, 2009;Cayuela and Pérez-Camino, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…León et al [51] studied the intact olive VIS/NIR spectra (400-1700 nm) for evaluation of oil, moisture, oleic acid, and linoleic acid contents. They compared spectra from different female parent trees and harvest year.…”
Section: A12 Content and Factors Related To Contentmentioning
confidence: 99%